UPAYA MENINGKATKAN READING HABIT SISWA PADA PEMBELAJARAN IPS MELALUI MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION - Iis Rojiah (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2021)
This study aims to improve students' reading habits in social studies learning through the Cooperative Integrated Reading and Composition (CIRC). This research is a classroom action research (CAR) held for class VII-C students of SMP Negeri 1 Sukasari in the 2019/2020 academic year, consisting of 41 students. CAR design refers to the model developed by Kemmis and Mc. Taggart, which consists of two cycles. Each cycle consists of four activities: planning, implementing actions, observing, and reflecting cycles. The criteria for the success of the action if most or at least 70% of students have good reading habits. The results showed that: 1) The reading frequency of students in the first cycle was 56% and in the second cycle was 65%, 2) The reading intensity of the students in the first cycle was 56%, and in the second cycle was 74%, 3) The students' reading interest in the first cycle is 67%, and in the second cycle is 76%, 4) The accuracy of students' reading strategies in the first cycle is 63%, and in the second cycle is 76%, and 5) The diversity of students' reading types in the first cycle is 61%, and in the second cycle by 84%. Thus, the average percentage of students' reading habits in the first cycle was 61%, while in the second cycle, it was 75%.